Aquaculture in Sri Lanka: History, current status and future potential - Asbjørn Drengstig (International Journal of Aquaculture and Fishery Sciences - Peertechz Publications, 2020)
The World Food and Agriculture Organisation (FAO) [1] predict that the world's population will reach over 9 billion within 2050, which is approximately 34% higher than today. Nearly all this population increase is expected to occur in developing countries. Urbanization will also continue at an accelerated pace, and about 70% of the world's population will become urban over next 3 decades (compared to 49% today). In addition, income levels in 2050 will be many multiples of what they are now. Hence, the biggest challenge in the future will be to find ways to feed this larger, more urban, and richer population. FAO has forecasted sea catches to stop growing at 85 - 90 million tonnes a year and all incremental demands would have to be met by culturing.